Association of media literacy with cigarette smoking among youth in Jujuy, Argentina - Salgado, Maria Victoria (2012)
Introduction: Latin America has the highest prevalence of tobacco use by youth. Higher media literacy, defined as the ability to analyze and evaluate media messages, has been associated with lower smoking among youth in the United States. The objective of this study was to determine whether media literacy related to smoking is independently associated with current smoking and susceptibility to future smoking in a sample of mostly indigenous youth in Jujuy, Argentina. Methods: In 2006, a self-administered survey was conducted among 10th grade students sampled from 27 randomly selected urban and rural schools in Jujuy. Survey items measured smoking behavior (ever, never, and current), susceptibility to future smoking among never-smokers (definitely not accept a cigarette from a friend or to smoke in the future), 5 items assessing smoking media literacy (SML), and risk factors for smoking. Results: Of the 3,470 respondents, 1,170 (34%) reported having smoked in the previous 30 days (current). Of the 1,430 students who had never smoked, 912 (64%) were susceptible to future smoking. High media literacy was present in 38%. Using multiple logistic regression, fully adjusted models showed that high media literacy was significantly associated as a protective factor of being a current smoker (odds ratio [OR] = 0.81; 95% CI = 0.67–0.97) and of being susceptible to future smoking (OR = 0.73; 95% CI = 0.58–0.92) among those who had never smoked. Conclusions: Among youth in Jujuy, higher SML was significantly associated with both lower current smoking and susceptibility to future smoking. Teaching SML may be a valuable component in a prevention intervention in this population.